Lurching towards a canon: Mahāyāna Sūtras in Khotanese garb - Chen, Ruixuan (Entangled Religions, 2021)
The concept of canon centers around authority. Assertions about canonicity both reflect and reshape the structure and the source of authority. In a Buddhist context, processes of canonization are highly fluid and complex, shedding light on the socio-religious landscapes of different Buddhist cultures. The present essay explores the complexities of canonization by focusing on a specific Buddhist culture on the ancient Silk Routes, where Mahāyāna sūtras, a collection of Buddhist literature of disputed authenticity in India, were accepted as scriptural and canonized in a remarkable manner. Through the lens of an indigenous Buddhist poem, the author argues that the reception and canonization of Mahāyāna sūtras give illuminating clues about a pivotal transition in the history of this Buddhist kingdom named Khotan, where both the removal and the bestowal of authority took place.